The Role of NMNAT2/SARM1 in Neuropathy Development - Olga Tarasiuk; Laura Molteni; Alessio Malacrida; Gabriella Nicolini (Biology, 2024)
Chemotherapy-induced peripheral neuropathy (CIPN) commonly arises as a side effect of diverse cancer chemotherapy treatments. This condition presents symptoms such as numbness, tingling, and altered sensation in patients, often accompanied by neuropathic pain. Pathologically, CIPN is characterized by an intensive “dying-back” axonopathy, starting at the intra-epidermal sensory innervations and advancing retrogradely. The lack of comprehensive understanding regarding its underlying mechanisms explains the absence of effective treatments for CIPN. Recent investigations into axon degeneration mechanisms have pinpointed nicotinamide mononucleotide adenylyltransferase 2 (NMNAT2) and sterile alpha and TIR motif-containing 1 protein (SARM1) as pivotal mediators of injury-induced axonal degeneration. In this review, we aim to explore various studies shedding light on the interplay between NMNAT2 and SARM1 proteins and their roles in the progression of CIPN.